Molecular markers of apoptosis in cancer patients exposed to ionizing radiation: the post-chornobyl view - Philchenkov, A.A.; Balcer-Kubiczek, E.K. (Experimental Oncology, 2016)
During the past three decades, the deleterious consequences of Chornobyl accident including carcinogenic effects in the people who were accidentally exposed to radiation have been intensively studied. In particular, recent studies provided increased knowledge of the molecular pathogenesis of thyroid tumors in children exposed to Chornobyl fallout. The risk of several forms of leukemia including myelodysplastic syndromes is elevated in Chornobyl liquidators. Furthermore, the upward trends of increases in a variety of other tumors including breast cancer, cancers of central nervous system and renal cancer have been reported in the persons exposed to Chornobyl fallout. There is growing evidence that insufficient apoptosis allows irradiated cells to survive and thereby contributes to carcinogenesis. The purpose of the present survey is to summarize the recent findings related to apoptotic biomarkers among cancer patients from the different populations affected by the Chornobyl catastrophe. Among the particularly radiosensitive cancer sites, we focused on thyroid cancer and leukemia. Several genes and/or proteins controlling apoptosis directly or indirectly have been incorporated into the analysis. The data reviewed here provide a mechanistic link between the apoptosis alterations and development of radiation-related cancer in the 30-year post-Chornobyl period. We suggest that the type of mutations arising from misrepair of DNA double strand breaks (gene fusion and amplification) is the initial signature event in radiation-induced thyroid cancer. Much work has to be done over the next years to elucidate central questions related to the nature of human radiation carcinogenesis. This article is part of a Special Issue entitled “The Chornobyl Nuclear Accident: Thirty Years After”.